Wage insurance as a policy option in the United States - Stephen A. Wandner (W.E. Upjohn Institute for Employment Research, 2016)
Wage insurance is a program that attempts to help permanently displaced workers transition to employment rapidly, effectively, and equitably. Because displaced workers have been found to suffer substantial earnings losses when they become reemployed, a wage insurance program provides a temporary wage supplement that partially reduces the wage loss experienced by targeted, newly reemployed workers. While participating workers receive a "wage supplement," the program is called "wage insurance" because of its design as a social insurance program rather than an income transfer program. This paper provides a discussion of the development of wage insurance as a policy option in the United States and proposals that have had varying goals and designs.
Keywords: J65; J68; 330; wage insurance; unemployment insurance; displaced workers; trade adjustment assistance; earnings losses; wage supplement